Examining the Factors Enhancing Green Growth in BRICS Economies: Interplay between Economic Globalization, Renewable Energy Use, and Government Efficiency - Neffati, Mohamed; Khemiri, Imen (International Journal of Energy Economics and Policy, 2025)
Studying economic green growth (EGG) and identifying its drivers have always been crucial for understanding Arabia’s sustainable economic development. Given Arabia’s extensive economic globalization process, potential impacts on the country’s green growth include government effectiveness and inward energy consumption. This study examines the effects of globalization, renewable energy, and institutional quality on green growth across BRICS+ countries from 1996 to 2021. This research mainly empirically explores that economic development, institutional quality, and globalization generally support green growth, while renewable energy offers long-term benefits despite short-term challenges. Non-renewable energy and environmental factors like population growth and forest areas have mixed or context-dependent impacts. Policies aimed at advancing renewable energy and improving energy efficiency have proven highly effective in reducing emissions. However, careful management is necessary to mitigate the environmental impact of free trade and dependence on non-renewable energy sources.